Distribution and diversity of glycocin biosynthesis gene clusters beyond Firmicutes. (2nd July 2020) - Singh, Vaidhvi; Rao, Alka
Abstract: Glycocins are the ribosomally synthesized glycosylated bacteriocins discovered and characterized in Firmicutes, only. These peptides have antimicrobial activity against several pathogenic bacteria, including Streptococcus pyogenes, methicillin-resistant Staphylococcus aureus and food-spoilage bacteria Listeria monocytogenes . Glycocins exhibit immunostimulatory properties and make a promising source of new antibiotics and food preservatives akin to Nisin. Biochemical studies of Sublancin, Glycocin F, Pallidocin and ASM1 prove that the nested disulfide-bonds are essential for their bioactivities. Using in silico approach of genome mining coupled with manual curation, here we identify 220 new putative glycocin biosynthesis gene clusters (PGBCs) spread across 153 bacterial species belonging to seven different bacterial phyla. Based on gene composition, we have grouped these PGBCs into five distinct conserved cluster Types I–V. All experimentally identified glycocins belong to Type I PGBCs. From protein sequence based phylograms, tanglegrams, global similarity heat-maps and cumulative mutual information analysis, it appears that glycocins may have originated from closely related bacteriocins, whereas recruitment of cognate glycosyltransferases (GTs) might be an independent event. Analysis further suggests that GTs may have coevolved with glycocins in cluster-specific manner to define distinctive donor specificities of GTs or to contribute to glycocin diversity across these clusters. We further identify 162 hitherto unreported PGBCs wherein the corresponding product glycocins have three or less than three cysteines. Secondary structure predictions suggest that these putative glycocins may not form di-nested disulfide-bonds. Therefore, production of such glycocins in heterologous host Escherichia coli is feasible and may provide novel antimicrobial spectrum and or mechanism of action for varied applications.